2010
DOI: 10.3109/00016489.2010.536990
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells in sudden sensorineural hearing loss

Abstract: Circulating levels of EPCs were significantly lower in SSHL patients compared with controls. In particular, CD34+KDR+ cells and CD34+CD133+KDR+ cells were significantly reduced (p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…The aetiology of ISSHL is still unclear and there are different hypothesis about risk factors for this condition [ 3 ]. We have previously demonstrated an increased expression of adhesion molecules, a reduced percentage of circulating endothelial progenitor cells and an altered FMD in ISSHL patients as early signs of endothelial damage [ 7 , 8 , 9 ]. We have hypothesized that the endothelial dysfunction could predispose to the development of a pro-thrombotic state at the level of the inner ear and considering that the cochlear vascular tree is a terminal type, an interruption of vascular flow due to endothelial damage impairs cochlear membrane functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aetiology of ISSHL is still unclear and there are different hypothesis about risk factors for this condition [ 3 ]. We have previously demonstrated an increased expression of adhesion molecules, a reduced percentage of circulating endothelial progenitor cells and an altered FMD in ISSHL patients as early signs of endothelial damage [ 7 , 8 , 9 ]. We have hypothesized that the endothelial dysfunction could predispose to the development of a pro-thrombotic state at the level of the inner ear and considering that the cochlear vascular tree is a terminal type, an interruption of vascular flow due to endothelial damage impairs cochlear membrane functions.…”
Section: Discussionmentioning
confidence: 99%
“…Rudack et al [ 6 ] have reported that elevated fibrinogen levels, smoking and the glycoprotein Ia C807T polymorphism are associated with an increased risk for this syndrome. Our group has previously reported that patients affected by ISSHL present higher serum levels of circulating adhesion molecules (sICAM-1 and sVCAM-1) [ 7 ], a reduced percentage of circulating endothelial progenitor cells [ 8 ] and an altered flow-mediated-dilatation (FMD) [ 9 ] as clear early markers of endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, the blood supply to the inner ear is a terminal circulation and given the lack of collateral circulation, any even partial occlusion of the AICA (anterior inferior cerebellar artery) or VBA (vertebrobasilar artery) can cause an ischaemic event in the inner ear 11 . Recently, patients with idiopathic sudden hearing loss were shown to have significantly lower flow-mediated dilation of the brachial artery than controls (5.6 ± 1.6 vs. 7.7 ± 3.7; p < 0.01) 14 , significantly lower levels (p = 0.018) of endothelial progenitor cells 15 and increased plasma levels of adhesion molecules, which is an early sign of endothelial dysfunction 16 .…”
Section: Discussionmentioning
confidence: 99%
“…While we already know that these cells are reduced in patients with vascular risk factors, this study confirmed that endothelial dysfunction is involved in the creation of SSNHL and the presence of vascular damage in patients supported. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%